Benchmarking Pain Outcomes for Children with Sickle Cell Disease Hospitalized in a Tertiary Referral Pediatric Hospital - Abi Vijenthira; Jennifer Stinson; Jeremy Friedman; Lori Palozzi; Anna Taddio; Dennis Scolnik; Charles Victor; Melanie Kirby-Allen; Fiona Campbell (Pain Research and Management)
BACKGROUND: Painful vaso-occlusive crisis (VOC) is the most common reason for hospitalization in children with sickle cell disease.